External cervical resorption: part 2 – management. (9th June 2018) - Patel, S.; Foschi, F.; Condon, R.; Pimentel, T.; Bhuva, B.
Abstract: Effective management of external cervical resorption (ECR) depends on accurate assessment of the true nature and accessibility of ECR; this has been discussed in part 1 of this 2 part article. This aim of this article was firstly, to review the literature in relation to the management of ECR and secondly, based on the available evidence, describe different strategies for the management of ECR. In cases where ECR is supracrestal, superficial and with limited circumferential spread, a surgical repair without root canal treatment is the preferred approach. With more extensive ECR lesions, vital pulp therapy or root canal treatment may also be indicated. Internal repair is indicated where there is limited resorptive damage to the external aspect of the tooth and/or where an external (surgical) approach is not possible due to the inaccessible nature of subcrestal ECR. In these cases, root canal treatment will also need to be carried out. Intentional reimplantation is indicated in cases where a surgical or internal approach is not practical. An atraumatic extraction technique and short extraoral period followed by 2‐week splinting are important prognostic factors. Periodic reviews may be indicated in cases where active management is not pragmatic. Finally, extraction of the affected tooth may be the only option in untreatable cases where there are aesthetic, functional and/or symptomatic issues.